Females do not have increased risk of early or late mortality after isolated aortic valve replacement: Results from a multi-institutional Australian study - Saxena, A.; Dinh, D.; Smith, J.; Reid, Christopher; Shardey, G.; Newcomb, A. (2013)
Aim. There is controversy regarding whether isolated aortic valve replacement (AVR) in women is associated with an increased risk of early and late mortality. The current study evaluates the impact of gender as an independent risk factor for early and late mortality after isolated AVR. Methods. Data obtained between June 2001 and December 2009 by the Australasian Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database Program was retrospectively analysed. Demographic, operative data and postoperative complications were compared between male and female patients using ?2 and t-tests. Long-term survival analysis was performed using Kaplan Meier survival curves and the log rank test. Independent risk factors for short term and long term mortality were identified using binary logistic and Cox regression, respectively. Results. Isolated aortic valve replacement was undertaken for 2790 patients in 18 Australian insitutions; 41.9% were female. Female patients were generally older (mean age 72 vs. 66 years (P<0.001) and presented more often with hypertension (P<0.001) and obesity (P<0.001). They were less likely to present with cerebrovascular disease (P=0.018), renal failure (P=0.017) and non-elective presentation (P=0.017). Women were observed to have a lower 30-day mortality (1.7% vs. 2.1%) but there was no difference on univariate (P=0.490) or multivariate analysis (P=0.983). There was no difference in the incidence of early complications but women were more likely to require red blood cell transfusion (P<0.001). Long-term survival was comparable between men and women (P=0.662). Conclusion. Female patients undergoing isolated AVR do not have an increased risk of early and late mortality. Further investigation is required to delineate the impact of gender on early and late outcomes following AVR.